The Bureau of Vocational Education its birth and development 1963-1972 - Niporn Yoma 1937- (1973)
The Bureau of Vocational Education was established in 1963 by Republic Act No. 3742 due to unequal distribution of wealth, increasing demand of the industrial sector for skilled manpower which the slow rate of growth of the labor force could not meet, and other economic, educational, socio-political and socio-cultural factors. Vocational schools and vocational graduates have increased with number but did not result in meeting demands of the economy for skilled manpower because the Bureau's supervisory activities, course offerings, extension services, placement of graduates, expansion of programs and cooperative activities with other sectors are far from satisfactory. Its most serious problems are inadequacy of funds, lack of qualified personnel, squatting in school sites, transportation facilities, textbooks, unwarranted establishment and conversion of vocational schools into chartered state colleges and universities, misdirection of vocational courses, and unfavorable attitudes toward vocational education.
Vita.
Thesis (M.A. Educational Administration)--University of the Philippines, Diliman.
Keywords: Vocational education -- Philippines -- History